Establishment of inclusive single-cell transcriptome atlases from mouse and human tooth as powerful resource for dental research - Hermans, Florian; Bueds, Celine; Hemeryck, Lara; Lambrichts, Ivo; Bronckaers, Annelies; Vankelecom, Hugo (Frontiers in Cell and Developmental Biology, 2022)
Single-cell (sc) omics has become a powerful tool to unravel a tissue’s cell landscape across health and disease. In recent years, sc transcriptomic interrogation has been applied to a variety of tooth tissues of both human and mouse, which has considerably advanced our fundamental understanding of tooth biology. Now, an overarching and integrated bird’s-view of the human and mouse tooth sc transcriptomic landscape would be a powerful multi-faceted tool for dental research, enabling further decipherment of tooth biology and development through constantly progressing state-of-the-art bioinformatic methods as well as the exploration of novel hypothesis-driven research. To this aim, we re-assessed and integrated recently published scRNA-sequencing datasets of different dental tissue types (healthy and diseased) from human and mouse to establish inclusive tooth sc atlases, and applied the consolidated data map to explore its power. For mouse tooth, we identified novel candidate transcriptional regulators of the ameloblast lineage. Regarding human tooth, we provide support for a developmental connection, not advanced before, between specific epithelial compartments. Taken together, we established inclusive mouse and human tooth sc atlases as powerful tools to potentiate innovative research into tooth biology, development and disease. The maps are provided online in an accessible format for interactive exploration.